Irisin Levels are Not Affected by Physical Activity in Patients with Anorexia Nervosa - Hofmann, Tobias; Elbelt, Ulf; Ahnis, Anne; Kobelt, Peter; Rose, Matthias; Stengel, Andreas (Frontiers in Endocrinology, 2014)
Irisin was recently identified as muscle-derived hormone that increases energy expenditure. Studies in normal weight and obese subjects reported an increased irisin expression following physical activity, although inconsistent results were observed. Increased physical activity in a subgroup of patients with anorexia nervosa (AN) complicates the course of the disease. Since irisin could account for differences in clinical outcomes, we investigated irisin levels in anorexic patients with high and moderate physical activity to evaluate whether irisin differs with increasing physical activity. Hospitalized female anorexic patients (n = 39) were included. Plasma irisin measured by enzyme-linked immunosorbent assay and locomotor activity were assessed at the same time. Patients were separated into two groups (n = 19/group; median excluded): moderate and high activity (6331 ± 423 vs. 13743 ± 1047 steps/day, p < 0.001). The groups did not differ in body mass index (14.2 ± 0.4 vs. 15.0 ± 0.4 kg/m2), irisin levels (558.2 ± 26.1 vs. 524.9 ± 25.2 ng/ml), and body weight-adjusted resting energy expenditure (17.6 ± 0.3 vs. 18.0 ± 0.3 kcal/kg/day, p > 0.05), whereas body weight-adjusted total energy expenditure (46.0 ± 1.4 vs. 41.1 ± 1.1 kcal/kg/day), metabolic equivalents (METs, 1.9 ± 0.1 vs. 1.7 ± 0.1 METs/day), body weight-adjusted exercise activity thermogenesis (1.8 ± 0.5 vs. 0.6 ± 0.3 kcal/kg/day), duration of exercise (18.6 ± 4.7 vs. 6.2 ± 3.1 min/day), and body weight-adjusted non-exercise activity thermogenesis (21.6 ± 1.0 vs. 18.8 ± 0.8 kcal/kg/day) were higher in the high activity compared to the moderate activity group (p < 0.05). No correlations were observed between irisin and activity parameters in the whole sample (p > 0.05). In conclusion, the current data do not support the concept of irisin being induced by exercise, at least not under conditions of severely reduced body weight like AN.